N-Salicyl-amino acid derivatives with antiparasitic activity from Pseudomonas sp. UIAU-6B - Rajakulendran, Joy E.; Oluwabusola, Emmanuel Tope; Cerone, Michela; Smith, Terry K.; Adebisi, Olusoji O.; Adedotun, Adefolalu; Preet, Gagan; Soldatou, Sylvia; Deng, Hai; Ebel, Rainer; Jaspars, Marcel (Beilstein Journal of Organic Chemistry, 2025)
Pseudomonads strains represent a promising source of bioactive compounds with potential pharmaceutical applications. The necessity to find new drugs is underscored by the increased concern over antimicrobial resistance in the human system. In this study, we isolated two previously undescribed N-salicyl-amino acids as natural products (1 and 2) and other two new derivatives (3 and 4) from the organic extract of a culture broth in a modified starch–glucose–glycerol (SGG) medium of Pseudomonas sp. UIAU-6B. The structure of the new natural products, pseudomonins D–G (1–4) isolated alongside other three known compounds, pseudomonine (5), pseudomonin B (6) and salicylic acid (7), were elucidated based on high-resolution mass spectrometry, 1D and 2D NMR analyses. The absolute configurations of the threonine residue in compounds 1 and 2 were determined by Marfey’s analysis. Compound 4 displayed a very weak pan-trypanocidal activity against Trypanosoma brucei, Trypanosoma cruzi and Leishmania major with EC50 values of 101–137 μM, while compounds 2 and 5 showed modest activity against Leishmania major, but none of the remaining compounds showed activity at the highest concentrations tested. The plausible biosynthetic hypotheses toward the compounds were also proposed.
Keywords: antiparasitic activity; biosynthesis pathway; phenolic siderophores; Pseudomonas species; pseudomonine